The nature of abandoned land control regulations - Anggles, Santo Yosep; Warka, Made; Nasution, Krisnadi (Technium Social Sciences Journal, 2022)
This research is a normative legal research. Abandonment of land as regulated in LoGA and its implementing regulations PP No.11 of 2010, the enactment Job Creation Law and PP No. 20 of 2021 essentially brings legal certainty in its implementation, in fact as Article 180, 181 of the Job Creation Law and PP No.20 of 2021, there is still a need for a harmonization of laws and regulations, which means that there is no guarantee of legal certainty. As a result of law on controlling and utilizing abandoned land, with the harmonization of statutory regulations regarding abandoned areas and abandoned land, agrarian reform which still recognizes land reform as so far is intended for abandoned land in UUPA, makes the utilization of abandoned land.